2018
DOI: 10.1002/chem.201802303
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Catalysis: Highly Enantioselective Acetyl Aza‐arene Addition to Enals

Abstract: A novel catalytic enantioselective methodology based on synergistic catalysis for the synthesis of chiral 2-acyl pyridines and pyrazines is reported. The strategy involves the metal-Lewis acid activation of acetyl aza-arenes and the secondary-amine activation of enals. The proposed mechanism is supported by DFT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
(11 reference statements)
0
15
0
Order By: Relevance
“…A double synergistic Michael addition followed by an intramolecular aldol reaction and dehydration affords the final products in high yields, high diastereo‐ and enantioselectivities (97–99 % ee ) (Scheme 27). [56] …”
Section: Combining Aminocatalysis and Transition Metal Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…A double synergistic Michael addition followed by an intramolecular aldol reaction and dehydration affords the final products in high yields, high diastereo‐ and enantioselectivities (97–99 % ee ) (Scheme 27). [56] …”
Section: Combining Aminocatalysis and Transition Metal Catalysismentioning
confidence: 99%
“…The mechanism was supported by DFT calculations which suggested that zinc coordination also favors the interaction of HOMO of the enolate with the LUMO of the iminium ion and hence plays a key role in enolate addition to the iminium ion (Scheme 28). [56] …”
Section: Combining Aminocatalysis and Transition Metal Catalysismentioning
confidence: 99%
“…Furthermore, the group of Rios also successfully disclosed various strategies for the preparation of carbocycles type molecules. For instance, through the enantioselective ring expansion of vinyl cyclopropanes, providing highly substituted [86], formal ring contraction for the generation of spiropyrazolones 106 [87], the asymmetric synthesis of cyclopentanes with four stereogenic centers 108 [88], the enantioselective acetyl aza-arene addition to α,β-unsaturated aldehydes affording chiral 2-acyl pyridines and pyrazines 110 [89], or, very recently disclosed, the highly enantioselective cascade reaction for the synthesis of dihydroacridines 112 (Scheme 23) [90]. Topics in Current Chemistry (2019) 377:38…”
Section: Transition Metal-and Amine-catalyzed Carbocyclization Reactionsmentioning
confidence: 99%
“…Furthermore, the group of Rios also successfully disclosed various strategies for the preparation of carbocycles type molecules. For instance, through the enantioselective ring expansion of vinyl cyclopropanes, providing highly substituted spirocyclopentanes 104 [86], formal ring contraction for the generation of spiropyrazolones 106 [87], the asymmetric synthesis of cyclopentanes with four stereogenic centers 108 [88], the enantioselective acetyl aza-arene addition to α,β-unsaturated aldehydes affording chiral 2-acyl pyridines and pyrazines 110 [89], or, very recently disclosed, the highly enantioselective cascade reaction for the synthesis of dihydroacridines 112 (Scheme 23) [90].
Scheme 23Various chemical strategies for the preparation of various carbocyclic compounds
…”
Section: Transition Metal- and Amine-catalyzed Carbocyclization Reactmentioning
confidence: 99%